Alternative Expressions of Citizen Voices: The Protest Song and Popular Engagements with the Mozambican State - Manhiça, Anésio; Shankland, Alex; Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Tadros, Mariz (Institute of Development Studies, 2020)
This study examines Mozambican popular music to investigate three questions: Are notions of empowerment and accountability present in popular music in Mozambique? If so, what can these existing notions of empowerment and accountability reveal about relations between citizens and state institutions in general and about citizen-led social and political action in particular? In what ways is popular music used to support citizen mobilisation in Mozambique? The discussion is based on an analysis of 46 protest songs, interviews with musicians, music producers and event promoters as well as field interviews and observations among audiences at selected popular music concerts and public workshops in Maputo city. Secondary data were drawn from radio broadcasts, digital media, and social networks. The songs analysed were widely played in the past two decades (1998–2018), a period in which three different presidents led the country. Our focus is on the protest song, conceived as those musical products that are concerned with public affairs, particularly public policy and how it affects citizens’ social, political and economic life, and the relationship between citizens and the state.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento

Sound of One Hand Clapping: Information Disclosure for Social and Political Action for Accountability in Extractive Governance in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (IDS, 2019)
Corruption through opaque public contracts costs Africa billions of dollars in revenue loss annually. Globally, initiatives to address this have centred on information disclosure (ID) but under what conditions does it work to promote accountability in the extractive sector that for a long time has seen its revenue management as being a major cause of conflict in Africa? Our study on this issue in Mozambique reveals intriguing findings, which suggest that protagonists of ID would need to recalibrate their strategies for promoting accountability. The study on ID in extractive governance in Mozambique has found 17 factors that connect to result in citizen and institutional inaction in demanding government accountability. The lessons from the study for policy and practice are that unless there is a link between ID and a government’s reputation, which scales up to the risk of a ruling government losing power, accountability is unlikely to occur when new information is disclosed.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; corruption / corrupção; decentralization / descentralização; extractive industries / indústrias extractivas; natural resources / recursos naturais

Theories of Change for Promoting Empowerment and Accountability in Fragile and Conflict-Affected Settings - Green, Duncan (IDS, 2017)
This paper explores the current state of thinking among a range of aid actors (multilaterals, bilateral, applied scholars and international non-governmental organisations) on how to promote empowerment and accountability in fragile, conflict and violence affected settings. It seeks to identify trends, gaps and weaknesses in that thinking, and propose research questions and hypotheses to test. Three underlying sources of confusion are identified that are hindering progress on both understanding empowerment and accountability in fragile, conflict and violence affected settings, and taking helpful action to promote it. They are: (1) theory of endogenous change (e.g. on how empowerment and accountability arise in situ) versus the theory of action of an external intervention; (2) fragility versus conflict: there is no clear justification for combining these different aspects into a single category; and (3) empowerment versus accountability: donor analysis and practice has been overwhelmingly weighted towards accountability, exhibiting limited understanding or interest in the nature of power.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; conflict / conflito; empowerment / empoderamento; fragility / fragilidade